Carapace color affects carotenoid composition and nutritional quality of the Chinese mitten crab, Eriochier sinensis. (May 2020) - Li, Qingqing; Zu, Lu; Cheng, Yongxu; Wade, Nicholas M.; Liu, Jianguo; Wu, Xugan
Abstract: The raw carapace color of Eriocheir sinensis is normally greenblack, while a small percentage of wild crabs have a purple carapace that also attract a higher market price. This study was conducted to quantify color parameters, carotenoids composition, and nutritional composition between purple and greenblack crabs. The redness ( a* ) values, total astaxanthin and astaxanthin ester content ( P  < 0.05) of the carapace, hepatopancreas, and ovaries of purple crabs was significantly higher than those of greenblack crabs. Irrespective of sex, purple crabs had higher ester astaxanthin/total astaxanthin ratios in all tissues than greenblack crabs. Interestingly, female purple crabs had the significantly higher percentage of eicosapentanoic acid (EPA) and lower ratio of n-6/n-3 polyunsaturated fatty acids (PUFA) in all edible parts than greenblack crabs, while male purple crabs had the significantly higher arachidonic acid (ARA) levels than greenblack crabs. In conclusion, purple crabs have the better nutritional quality than greenblack crabs. Highlights: The purple Eriocheir sinensis was significantly redder than greenblack. The astaxanthin content of purple crabs was significantly higher than greenblack. The EPA and ARA content of purple crabs was significantly higher than greenblack. The purple crabs have the better nutritional quality than greenblack.